2007
DOI: 10.4012/dmj.26.316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Cycling on Surface Texture of Restorative Composite Materials

Abstract: The purpose of this study was to evaluate the effect of thermal cycling on the surface texture of restorative materials. Disk-shaped specimens made of seven resin composites (Beautifil: BF; Esthet-X: EX; Filtek Supreme: FS; Inten-S: IS; Point 4: PT; Solare: SR; and Venus: VS) were finished with 1-μm alumina suspension, and then thermocycled between 4 and 60 ℃ in distilled water for 20,000 or 50,000 cycles with a dwell time of 60 seconds. Staining susceptibility and mean surface roughness, Ra, were examined, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 17 publications
1
44
1
6
Order By: Relevance
“…It has been shown that thermal stress and acidic challenges may affect the surface integrity of the composite resins and render them susceptible to discoloration. 44,45 As composite resin restorations in oral cavity endure thermal stress and acidic challenges associated with ingesting hot and cold acidic beverages on a daily basis, any color stability study model must consider the effects of changing temperatures and pH values. As common beverages and foods are in a multitude of combinations of colors, immersion of composite resin discs in a single type of colored fluid does not reflect the staining potential of human drinking and eating behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that thermal stress and acidic challenges may affect the surface integrity of the composite resins and render them susceptible to discoloration. 44,45 As composite resin restorations in oral cavity endure thermal stress and acidic challenges associated with ingesting hot and cold acidic beverages on a daily basis, any color stability study model must consider the effects of changing temperatures and pH values. As common beverages and foods are in a multitude of combinations of colors, immersion of composite resin discs in a single type of colored fluid does not reflect the staining potential of human drinking and eating behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Both thermal stress and pH variations may affect the surface and structural integrities of composite resin materials and render the restorations more susceptible to staining and discoloration. 44,45 As experimental testing in vitro remains to be a vital tool in assessing the color stability and stain resistance of new aesthetic restorative materials, it is important to devise a new model that considers the effects of thermal stress, pH variation, complexity of dietary colorants, and dynamic nature of fluid flow and allows differentiation of adsorption from absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The variation of filler exposure after thermal cycling is probably due to matrix degradation, which causes the exposure of the filler particles within and thus, results in higher roughness values . Several investigations have focused on the effects of thermocycling on microhardness, roughness, and color of composite restorations . Dos Santos and colleagues reported that 3,000 thermal cycles increased roughness values for all resin‐based composites and there was a tendency for reduced surface roughness values after 10,000 thermal cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In the regular oral functioning of eating and drinking, restorative materials are exposed to thermal stress 13 . In theory, thermal cycling simulates in vivo aging of the restorative material submitted to repeated cyclic exposure of hot and cold temperatures 14 …”
Section: Introductionmentioning
confidence: 99%